Interaksi Antarmanusia melalui Media Sosial Facebook Mengenai Topik Keagamaan - Benedictus A Simangunsong (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2016)
Human interaction has shifted with the advent of new media, the internet, especially with the presence of social media. The keyword of social media is a medium intended to share among individuals in order to achieve a better quality of life. The resarch aims finding human interaction trend influenced by social media i.e. Facebook, by looking at the content of the message delivered in sensitive issues phenomena, such as religious belief. Data analysis has been done through descriptive qualitative based on Martin Buber. These result indicates that interaction model can be established if the content of the message delivered in accordance with the wishes of communication, often obtained a description of the interaction that can be done by users against other users so that the purpose of the use of social media can be achieved.